De-Targeting: Advertising an Assortment of Products to Loss-Averse Consumers - Heiko Karle; Martin Peitz (University of Mannheim, Department of Economics, 2016)
We consider product markets in which consumers are interested only in a specific product category and initially do not know which product category matches their tastes. Using sophisticated tracking technologies, an intermediary can make inferences about a consumer's preferred product category and offer advertising firms the possibility to target their ads to match the consumer's taste. Such targeting reduces overall advertising costs and, as a direct effect, increases industry profits. However, as we show in this paper, when consumers form reference prices and are loss averse, more precise targeting may intensify competition between firms. As a result, firms may earn higher profits from "de-targeted" advertising; i.e., when the intermediary deliberately informs about some products and their price quotes from outside a consumer's preferred product category.
urn:nbn:de:bsz:180-madoc-402154
Keywords: L13; D43; M3; 330; Targeted advertising; Informative advertising; Consumer loss aversion; Reference prices; Contextual inference; Consumer recognition; Behavioral industrial organization